2011
DOI: 10.1152/japplphysiol.00141.2011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between leg muscle capillary density and peak hyperemic blood flow with endurance capacity in peripheral artery disease

Abstract: WR, Annex BH. Relationship between leg muscle capillary density and peak hyperemic blood flow with endurance capacity in peripheral artery disease. J Appl Physiol 111: 81-86, 2011. First published April 21, 2011 doi:10.1152/japplphysiol.00141.2011.-The aim of this study was to determine if skeletal muscle capillary density is lower in patients with peripheral artery disease (PAD) and if capillary density relates to functional limitations. PAD patients with intermittent claudication (IC) have a decreased exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 43 publications
6
100
2
Order By: Relevance
“…Previous findings of reduced muscle vascular endothelial growth factor protein content (26) and elevated thrombospondin-1 in the muscle (16) and muscle extracellular fluid (26) also provides some indication that the angiogenic potential of PAD-affected muscle may be impaired. However, the capillary-to-fiber ratio differed only nonsignificantly between the two groups, which is in contrast to other studies (16,45). This discrepancy may be a result of the presence of comorbidities or the age and physical activity levels of study participants and low group sample sizes but also of the muscle sampling site where the ischemic insult of PAD is likely to be less severe, and perhaps more variable, at the vastus lateralis than at the distal muscle groups, which have been sampled (3,16,45).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous findings of reduced muscle vascular endothelial growth factor protein content (26) and elevated thrombospondin-1 in the muscle (16) and muscle extracellular fluid (26) also provides some indication that the angiogenic potential of PAD-affected muscle may be impaired. However, the capillary-to-fiber ratio differed only nonsignificantly between the two groups, which is in contrast to other studies (16,45). This discrepancy may be a result of the presence of comorbidities or the age and physical activity levels of study participants and low group sample sizes but also of the muscle sampling site where the ischemic insult of PAD is likely to be less severe, and perhaps more variable, at the vastus lateralis than at the distal muscle groups, which have been sampled (3,16,45).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the capillary-to-fiber ratio differed only nonsignificantly between the two groups, which is in contrast to other studies (16,45). This discrepancy may be a result of the presence of comorbidities or the age and physical activity levels of study participants and low group sample sizes but also of the muscle sampling site where the ischemic insult of PAD is likely to be less severe, and perhaps more variable, at the vastus lateralis than at the distal muscle groups, which have been sampled (3,16,45). It should be noted that some studies have likewise failed to demonstrate such capillary rarefaction in IC patients compared with controls (21,30).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Impairment of the hyperemic blood flow response is associated with functional impairment in PAD. 53 There is evidence connecting greater brachial flowmediated dilation to greater physical activity in daily life in patients with PAD. 54 Recent studies related impaired brachial flow-mediated dilation with reduced self-reported walking ability and 6-minute walk test.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…These exercise improvements are not correlated with changes in limb hemodynamics but may be associated with changes in skeletal muscle metabolism and capillary density. 22,23 In contrast, revascularization results in substantial improvements in limb blood flow and oxygen delivery, but these improvements in limb flow are not well correlated with the change in exercise performance. 24 The recognition that a limitation in maximal exercise performance is a direct result of a complex pathophysiology and that both endurance and submaximal exercise performance are inherently impaired when maximal performance is limited has important implications for considering how to assess function and response to treatment in these patients.…”
Section: Pathophysiology Of the Exercise Limitation In Padmentioning
confidence: 99%